Apache Maven beginner to guru - Thompson, John (Packt Publishing, 2019)
"Apache Maven is the most popular Java build tool. Companies and open source communities around the world consider Apache Maven the 'go-to' build tool for their Java projects. In this course, you will gain comprehensive insights into Apache Maven for building and deploying your apps. You'll explore Maven build lifecycles, before going on to understanding how to use Maven to build and package Java projects. The course will then demonstrate how to use Maven with popular alternative JVM languages including Groovy, Kotlin, and Scala. Next, you will configure Maven to run your unit and integration tests written in JUnit 3, JUnit 4, JUnit 5, TestNG, and Spock. You will then delve into generating source code from XML and JSON schemas. In addition to this, the course will get you started with leveraging annotation processing at compile time for Project Lombok and Mapstruct. The course will help you further build on your knowledge with insights into the Apache Maven plugin system, along with guiding you through how plugins are used in the build lifecycle. From building Spring Boot apps, and improving code quality with code coverage and spot bug reports, through to unlocking the capabilities of the Spring Boot Maven plugins, this course helps you learn efficiently at your own pace. Finally, you'll be able to deploy project artifacts to Maven repositories, and later develop multi-module Maven projects. By the end of this course, you will have comprehensive knowledge of Apache Maven, along with the skills to use it for developing and deploying robust applications."--Resource description page
Title from resource description page (Safari, viewed February 20, 2020)
Keywords: Apache Maven; Java (Computer program language); Application software -- Development; Java (Langage de programmation); Logiciels d'application; Développement; Application software; Development; Electronic videos